OPTIMAL CONDITIONS FOR PREPARING CIGS THIN FILM THROUGH TWO-STEPPROCESS OF SPUTTERING FOLLOWED BY SELENIZATION - MORADI, M.; ZAHEDIFAR, M.; GHORBANI, T.; SAADAT, M.; ROSTAMI, K. (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Cu(In,Ga)Se2 films were prepared via a sputtering route followed by a selenization process, on glass substrates. Having a layer sequence Mo/In/Cu-Ga with preferred thicknesses, the metallic layers were selenized at vacuum of 6×10-3 mbar and 1 atm pressure with a total gas inlet of 7 sccm. Under vacuum, only single-phase CIGS was observed while at 1 atm, other phases in addition to CIGS were formed. The metallic layers were selenized at several temperatures. Pure-phased CIGS films were obtained by selenization at 600˚C. The crystallinity of the obtained films was further enhanced by increasing the selenization temperature. The produced CIGS films were studied by X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersion spectroscopy (EDS) techniques.